2015
DOI: 10.1371/journal.pone.0125945
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Trichuris muris Infection in C57BL/6 Mice Causes Significant Changes in Host Microbiota and Metabolome: Effects Reversed by Pathogen Clearance

Abstract: Trichuris species are a globally important and prevalent group of intestinal helminth parasites, in which Trichuris muris (mouse whipworm) is an ideal model for this disease. This paper describes the first ever highly controlled and comprehensive investigation into the effects of T. muris infection on the faecal microbiota of mice and the effects on the microbiota following successful clearance of the infection. Communities were profiled using DGGE, 454 pyrosequencing, and metabolomics. Changes in microbial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
230
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(257 citation statements)
references
References 56 publications
26
230
1
Order By: Relevance
“…Indeed, chronic T. muris infection results in the accumulation of interferon-g þ T cells in the bone marrow, 213 and does not appear to protect against the development of colitis. 214,215 Furthermore, depending on the strain, chronically infected mice gain less weight than their uninfected counterparts, 216 and in some cases even acquire colitis-like symptoms, thus losing weight, 217 mirroring the malnutrition and wasting of some infected humans. In contrast, lung pathology appears to be decreased in response to papain challenge, 218 illustrating that worm-induced protection against inflammatory disorders is highly context specific.…”
Section: Resolutionmentioning
confidence: 99%
“…Indeed, chronic T. muris infection results in the accumulation of interferon-g þ T cells in the bone marrow, 213 and does not appear to protect against the development of colitis. 214,215 Furthermore, depending on the strain, chronically infected mice gain less weight than their uninfected counterparts, 216 and in some cases even acquire colitis-like symptoms, thus losing weight, 217 mirroring the malnutrition and wasting of some infected humans. In contrast, lung pathology appears to be decreased in response to papain challenge, 218 illustrating that worm-induced protection against inflammatory disorders is highly context specific.…”
Section: Resolutionmentioning
confidence: 99%
“…14 The importance of a mucus niche for this bacterium can be seen as its abundance is increased during mucus overproduction in helminth infections. 15,16 Mucispirillum has been suggested to be associated with a healthy gut. 17 Comparison of the microbiota composition in the two colonies revealed differences but only a few candidates possibly contributing to the formation of an impenetrable mucus layer were identified.…”
Section: Bacteria With Potential To Affect the Mucus Propertiesmentioning
confidence: 99%
“…14 The importance of a mucus niche for this bacterium can be seen as its abundance is increased during mucus overproduction in helminth infections. 15,16 Mucispirillum has been suggested to be associated with a healthy gut. 17…”
mentioning
confidence: 99%
“…For example, 3 independent laboratories reported that infection with the mouse duodenal parasite Heligmosomoides polygyrus expanded the proportion of Lactobacillaceae and Enterobacteriaceae in the gut [35 • ]. Moreover, while chronic infection with the mouse whipworm Trichuris muris similarly raised Lacto-bacillaceae representation, it also reduced overall microbiota diversity, a factor often associated with poorer homeostatic control, reflecting an ecological imbalance in the intestinal microbial community [6,7 • ]. Intriguingly, removal of parasites restored the ‘naïve’ flora observed in uninfected mice, suggesting that helminth-induced changes in the microbiota are reversible by clearance of the macrobiota [7 • ].…”
mentioning
confidence: 99%
“…Moreover, while chronic infection with the mouse whipworm Trichuris muris similarly raised Lacto-bacillaceae representation, it also reduced overall microbiota diversity, a factor often associated with poorer homeostatic control, reflecting an ecological imbalance in the intestinal microbial community [6,7 • ]. Intriguingly, removal of parasites restored the ‘naïve’ flora observed in uninfected mice, suggesting that helminth-induced changes in the microbiota are reversible by clearance of the macrobiota [7 • ]. Likewise, in wild mice ( Apodemus flavicollis ) a correlation was observed between increased bacterial microbiota richness and helminth infections and different types of helminths elicited characteristic changes in the composition and abundance of microbiota species [8].…”
mentioning
confidence: 99%